BMP Pathway Regulation of and by Macrophages - Talati, Megha (Public Library of Science, 2014)
Pulmonary arterial hypertension (PAH) is a disease of progressively increasing pulmonary vascular resistance, associated with mutations of the type 2 receptor for the BMP pathway, BMPR2. The canonical signaling pathway for BMPR2 is through the SMAD family of transcription factors. BMPR2 is expressed in every cell type, but the impact of BMPR2 mutations affecting SMAD signaling, such as Bmpr2(delx4+), had only previously been investigated in smooth muscle and endothelium. In the present study, we created a mouse with universal doxycycline-inducible expression of Bmpr2(delx4+) in order to determine if broader expression had an impact relevant to the development of PAH. We found that the most obvious phenotype was a dramatic, but patchy, increase in pulmonary inflammation. We crossed these double transgenic mice onto an NF-κB reporter strain, and by luciferase assays on live mice, individual organs and isolated macrophages, we narrowed down the origin of the inflammatory phenotype to constitutive activation of tissue macrophages. Study of bone marrow-derived macrophages from mutant and wild-type mice suggested a baseline difference in differentiation state in Bmpr2 mutants. When activated with LPS, both mutant and wild-type macrophages secrete BMP pathway inhibitors sufficient to suppress BMP pathway activity in smooth muscle cells (SMC) treated with conditioned media. Functionally, co-culture with macrophages results in a BMP signaling-dependent increase in scratch closure in cultured SMC. We conclude that SMAD signaling through BMP is responsible, in part, for preventing macrophage activation in both live animals and in cells in culture, and that activated macrophages secrete BMP inhibitors in sufficient quantity to cause paracrine effect on vascular smooth muscle.